Extracellular matrix–inspired gelatin/hyaluronic acid injectable hydrogels. Issue 6 (13th April 2017) - Sanmartín-Masiá, Esther; Poveda-Reyes, Sara; Gallego Ferrer, Gloria
ABSTRACT: Gelatin injectable hydrogels have attracted attention for soft tissues regeneration; however, their poor mechanical properties limit their applications. The authors present a versatile strategy to enhance mechanical properties by mixing gelatin (Gel) with different proportions of hyaluronic acid (HA). The protein-polysaccharide systems are inspired by extracellular matrix and benefit from adhesive properties of RGD sequences in Gel and enhanced hydration and stiffness of HA. The authors were able to raise the Young's modulus from 4 kPa to 6 kPa and gelation times can be tuned between 4 to 9 min, giving surgeons the option of adapting the material to specific requirements. GRAPHICAL ABSTRACT: